APPLICATION OF INFORMATION TECHNOLOGIES IN MEDICINE: ELECTRONIC HEALTH SYSTEMS - Shodmonova Sokhibakhon Muhammedovna (Bright Mind Publishing, 2025)
This article broadly covers modern trends in the use of information technologies in the medical field, in particular, the importance of electronic health systems (e-Health). Electronic health systems effectively organize information exchange between doctors, patients and healthcare institutions, improve the quality of services and expand their use. The study separately analyzes such areas as electronic medical records, telemedicine, mobile health applications, databases and artificial intelligence-based diagnostic systems. It also considers the advantages, existing problems and prospects of implementing electronic health systems, and their application in the conditions of Uzbekistan. The results of the article are aimed at developing innovative approaches in medicine and formulating recommendations for more effective implementation of information technologies.
Keywords: Information technology, electronic health system, e-Health, telemedicine, electronic medical card, mobile health applications, artificial intelligence, medical database, diagnostics, healthcare, innovative approach, digital medicine, efficiency.